The Characterization and optimization of cellulose/ carboxymethycellulose (CMC)- based hydrogel from peanut shells (arachis hypogaea) as a controlled-release fertilizer for urea. - Victoria, E.N.E.G., Cajanding, B. L. T., Dianko, R.J. U., Eusebio, M.L.C., Mendoza, J.A.T. 4 0 16; 5
ABSTRACT: Water scarcity and the increasing heat index must be addressed for agriculture to be sustainable, hence strategies for improving nutrient use and water holding capacity in farming fields had become necessary. In response to these challenges, in this study, a controlled release fertilizer cellulose extracted from peanut (Arachis hypogaea) shells, citric acid as a crosslinker and carboxymethyl cellulose (CMC as a gelling agent. For the optimization of hydrogel, five (5) different ratios of cellulose/CMC hydrogels were synthesized, taking into consideration the spectra, swelling ratio and gel fraction of each ratio. Successful crosslinking of cellulose and CMC using citric acid was confirmed with the FTIR spectra of the synthesized hydrogel. The optimal hydrogel was characterized using gravimetric and surface analytical analysis. The soil moisture content in the presence of the optimal hydrogel, C40, determined using gravimetric analysis, revealed that the presence of hydrogel elevated soil moisture content by 20%. A maximum swelling ratio of 50.71% was achieved for the optimal hydrogel, C40. Scanning electron microscope (SEM) analysis revealed that the synthesized optimal hydrogel has a film-like non porous structure. Using urea as a fertilizer, the maximum loading capacity of urea in hydrogel was 0.418 g/g. The optimal cellulose/CMC hyfrogel, C40, was observed to enable the slow release of urea, following the zeroth order kinetic order and the Hixson - Crowell kinetic model as its kinetic model, over a period of five (5) daus after application. Hence, the study revealed that C40 has a notable loading capacity of urea and demonstrates controlled release on both soil and water, indicating its potential as a controlled-release fertilizer.
Undergraduate Thesis : (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2